2018
DOI: 10.1029/2018ef000843
|View full text |Cite
|
Sign up to set email alerts
|

Changing Seasonal Rainfall Distribution With Climate Directs Contrasting Impacts at Evapotranspiration and Water Yield in the Western Mediterranean Region

Abstract: Over the past century, climate change has been reflected in altered precipitation regimes worldwide. Because evapotranspiration is sensitive to both water availability and atmospheric demand for water vapor, it is essential to assess the likely consequences of future changes of these climate variables to evapotranspiration and, thus, runoff. We propose a simplified approach for annual evapotranspiration predictions, based on seasonal evapotranspiration estimates, accounting for the strong seasonality of meteor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 72 publications
1
31
0
Order By: Relevance
“…In contrast the sum of monthly fd approached 0 for Py < 550 mm (Figure 8), which resulted in a threshold for the water budget that ensured the survival of the trees in the ecosystem. Instead, as expected, annual ET was not sensitive to Py, ranging from 390-460 mm (Figure 8), in agreement with Montaldo and Oren (2018), because evapotranspiration variability in this Sardinian area is mainly controlled by the seasonal variability in precipitation (Montaldo and Oren, 2018). Finally, we also performed a sensitivity analysis of fd to uncertainties in the measured flux of Equation (6).…”
Section: Soil Water Balancesupporting
confidence: 56%
See 1 more Smart Citation
“…In contrast the sum of monthly fd approached 0 for Py < 550 mm (Figure 8), which resulted in a threshold for the water budget that ensured the survival of the trees in the ecosystem. Instead, as expected, annual ET was not sensitive to Py, ranging from 390-460 mm (Figure 8), in agreement with Montaldo and Oren (2018), because evapotranspiration variability in this Sardinian area is mainly controlled by the seasonal variability in precipitation (Montaldo and Oren, 2018). Finally, we also performed a sensitivity analysis of fd to uncertainties in the measured flux of Equation (6).…”
Section: Soil Water Balancesupporting
confidence: 56%
“…At present, the developed woody cover percentage (∼33%) of the Sardinian site is sustainable with the historical mean annual precipitation (MAP) (∼650 mm/y), according to Yang et al (2016) and Axelsson and Hanan (2017), who estimated sustainable woody cover percentages for a large range of MAP in Africa and Texas dry ecosystems. We demonstrated that drier conditions, such as those predicted by future climate change projections in the Mediterranean area (Cayan et al, 2008;Mariotti et al, 2008;Mastrandrea and Luers, 2012;May, 2008;Ozturk et al, 2015), with a reduction of MAP up to ∼15% in Sardinia (Montaldo and Oren, 2018), could impact the existing tree-grass ecosystem equilibrium, decreasing the woody cover spatial distribution.…”
Section: Discussionmentioning
confidence: 88%
“…This is reflected in the greater reliance on f d in the spring of 2017 relative to a normal spring (Figure 2). It stands to reason that, with scenarios predicting progressive decrease of winter precipitation and warmer springs over the next 70 years (Flato et al., 2013; Montaldo & Oren, 2018), the reliance of the grass patches on tree roots will increase, perhaps exceeding the capacity of tree clamps to provide sufficient water to maintain the current grass cover fraction. Indeed, in dry springs, ET decreased relative to typical springs, but only the grass surface temperature increased substantially (Figure 7c), suggesting increasing moisture stress.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study identified tree transpiration as the primary component of ET during the dry seasons – tree clumps maintained some summertime transpiration even though the thin soil was dry and its water content unchanging, suggesting access to subsoil water source. Indeed, the wild olive, a common Mediterranean species (Lumaret & Ouazzani, 2001; Terral et al., 2004), appear to tolerate well prolonged droughts (e.g., summer, 2003), increasingly common on the island (Montaldo & Oren, 2018; Montaldo & Sarigu, 2017). The species developed an adaptation strategy to increase reliance on a range of avoidance and tolerance mechanisms that maintain internal water status and metabolic activity during the dry periods (Connor et al., 2005; Fernandez et al., 1997; Lo Gullo & Salleo, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In a hot environment, the local ascent rate and atmospheric moisture availability can be constrained, resulting in negative scaling rates between precipitation and temperatures (Hardwick Jones et al, 2010). Simultaneously, both the vapor pressure deficit in the atmosphere and total vegetation water use can increase with warming, triggering intensified negative responses of runoff to climate change (Cook et al, 2020; Montaldo & Oren, 2018). Given that drought conditions are highly dependent on the atmospheric and terrestrial water budgets, the responses of monthly precipitation and runoff to climate warming play a key role in understanding such hazards and need to be adequately understood (Zhai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%